Measurement of Haemoglobin through processing of images of inner eyelid - Atique, Md Moin Uddin; Sarker, Md Rafiqul Islam; Rabbani, K Siddique e (Bangladesh Journal of Medical Physics, 2017)
Anaemia is a common disorder in which the percentage of haemoglobin in a persons blood decreases below a certain level. Sometimes in medical emergency, it is necessary to know the percentage of haemoglobin of a patient and it is usually done by laboratory testing of blood drawn from a vein, which is semi-invasive and time consuming. Doctors can make a quick approximate assessment from the redness of the inner lower eyelid, but it is not quantitative. However, it suggests that quantitative values may be obtained analyzing an optical image of the same, and was the aim of the present work. As a preliminary study, images of inner lower eyelids of 7 persons were obtained using two digital cameras (Nikon DSLR and Nokia phone) under a fixed lighting condition and the haemoglobin counts in their blood were obtained using standard blood tests. Using software developed for this work, several regions of size 10x10 pixels were manually chosen to avoid areas giving strong reflections of the incident light and the average red pixel values for all of these regions were determined. These values were plotted against the percentage of haemoglobin for the two cameras separately. Both the graphs showed similar behavior and respective linear trend lines were fitted to each which gave good correlations, the coefficients being 0.83 and 0.81 respectively. The green and blue pixel values did not give any reasonable trend and so were not studied further. If other variables, such as lighting and camera exposure can be kept fixed, it may be possible to improve the accuracy further. Bangladesh Journal of Medical Physics Vol.8 No.1 2015 7-13